Effects of the performance management system on service delivery in the Mbombela Local Municipality : Mpumalanga Province - Kgwefane, Nomathemba Gladys (My University, 2014)
The study seeks to determine whether the introduction of Performance Management System (PMS) in Mbombela Local Municipality (MLM), Mpumalanga Province has effects on service delivery. Municipalities tend to focus mainly on complying with legislative requirements of having an Integrated Development Plan (IDP) and PMS other than implementing the IDP and PMS to enhance the delivery of services to the community. The annual performance reports of MLM for the financial year 2009/2010 and 2010/2011 indicates performance targets in which some were achieved while in some cases the municipality failed to achieve. The Department of Cooperative Governance and Traditional Affairs (CoGTA) introduced the Performance Management Framework in municipalities with the aim of empowering communities to demand better services and hold municipalities accountable. In this regard a literature review was undertaken. In the literature review, it became evident that communities have displeasure in the delivery of services such as electricity, water, sanitation and roads. Further findings in the study indicate that the introduction PMS in MLM has not led to positive change in the delivery of services. Recommendations made in the study for MLM to enhance service delivery through PMS, include cascading PMS to all employees in MLM, change management and communication strategy. Further issues of alignment and integration of the IDP processes, budget, PMS, monitoring, evaluation and training on the formulation of Key Performance Areas and Key Performance Indicators are recommended.
Thesis (MPA.) -- University of Limpopo, 2014
Keywords: Service delivery; Performance management system; 658.3125; Performance -- Management; Performance standards; Goal setting in personnel management; Employees -- Rating of